ASPEK YURIDIS WANPRESTASI AKIBAT TIDAK MELAKUKAN PEMBAYARAN DALAM PERJANJIAN PENGERJAAN PEMBUATAN TAMAN AIR MANCUR (Studi Putusan Mahkamah Agung Nomor 1930 K/Pdt/2018) - Ryandi Bashkara (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2021)
The default in the implementation of chartering agreements is a phenomenon that often occurs in practice. Many factors cause a default; it can be due to the fault of the parties or the fault from the outside of the parties. The research problem in this thesis is what are the legal consequences if there is a default in the agreement for the construction of the fountain park, what are the obligations of the bouwheer in the agreement for the construction of the fountain park, how are the legal considerations of the judge in deciding the default in the contract for the construction of the fountain park.The results of the study indicate that the legal consequences if there is a default in the agreement to build a fountain park, then the aggrieved party makes a lawsuit so that the party causing the loss to complete the payment for the construction of the fountain park which has been completed The owner's obligation in the agreement for the construction of the fountain park is supervising and checking the implementation of the work which are carried out by the contractor, making payments according to the price stated in the contract, providing instructions according to the schedule and pay compensation for the mistakes made. The judge's legal considerations in deciding the default in the fountain park work contract agreement are PT. Barindo Utama has broken its promise for not to pay the remaining obligations to CV. Kertawijaya and as the owner of the Lubuklinggau City Government project cq the Lubuklinggau City Public Works Department do not have a legal relationship with CV. Kertawijaya because of the Work Order from PT. Barindo Utama to CV. Kertawijaya was published unbeknownst of Lubuklinggau City Government cq Lubuklinggau City Public Works Department.Keywords: Default, Agreement, Fountain.